Global legal pluralism : a jurisprudence of law beyond borders - Berman, Paul Schiff (Cambridge : Cambridge University Press, 2012)
'We live in a world of legal pluralism, where a single act or actor is potentially regulated by multiple legal or quasi-legal regimes imposed by state, substate, transnational, supranational, and nonstate communities. Navigating these spheres of complex overlapping legal authority is confusing, and we cannot expect territorial borders to solve all these problems because human activity and legal norms inevitably flow across such borders. At the same time, those hoping to create one universal set of legal rules are also likely to be disappointed by the sheer variety of human communities and interests. Instead, we need an alternative jurisprudence, one that seeks to create or preserve spaces for productive interaction among multiple, overlapping legal systems by developing procedural mechanisms, institutions, and practices that aim to manage, without eliminating, the legal pluralism we see around us. Such mechanisms, institutions, and practices can help mediate conflicts, and we may find that the added norms, viewpoints, and participants produce better decision making, better adherence to those decisions by participants and non-participants alike, and ultimately better real-world outcomes. Global Legal Pluralism provides a broad synthesis across a variety of legal doctrines and academic disciplines and offers a novel conceptualization of law and globalization'--Provided by publisher.
Introduction -- A world of legal conflicts -- The limits of sovereigntist territoriality -- Universalism and its discontents -- Towards a cosmopolitan pluralist jurisprudence -- Procedural mechanisms, institutional designs, and discursive practices for managing pluralism -- The changing terrain of jurisdiction -- A cosmopolitan pluralist approach to choice of law -- Recognition of judgments and the legal negotiation of difference -- Conclusion.
Includes bibliographical references (p. xi-xii) and index.
Keywords: Legal polycentricity; Law and globalization